$^1$H, $^13$C and $^15$N assignments of EGF domains 8–11 of human Notch-1 - Weisshuhn, P; Handford, P; Redfield, C (Springer Netherlands, 2015)
The Notch receptor is part of a core cell–cell signaling system crucial for development and tissue homeostasis in Metazoa. Structural information is available for the negative regulatory region, the ligand-binding region and the intracellular domain of Notch, but data for the remaining portions of the extracellular region which determine its overall shape at the cell surface are still lacking. This region consists of 36 EGF-like domains arranged as multiple tandem repeats. Most EGF-like domains near the ligand-binding domains EGF11 and 12 are of the calcium-binding type, with well-described, rigid and near-linear interdomain interfaces. However, EGF10 is a conserved, non-calcium-binding domain which may confer flexibility or a non-linear organization to the receptor. To probe this, we have expressed and purified a four-domain construct, EGF8–11, from human Notch-1, and report here the 1H, 13C and 15N resonance assignments. Differences in EGF11 chemical shifts between this construct and a previously assigned construct, EGF11–13, confirm the presence of hydrophobic interdomain contacts between the hairpin turn of the major β-sheet in EGF11 and the conserved aromatic residue within the C-terminal region of EGF10. This suggests that the EGF10–11 interface is rigid.